Foreigner’s satisfaction towards tourism Malaysia Pahang’s services / Nadia Farhan Mohd Shalahim - Mohd Shalahim, Nadia Farhan (Faculty of Business and Management, 2010)
Tourism industry is one of the major contributors to the national income. Pahang is strongly dependent on tourism industry in order to generate economic growth. Therefore, the purpose of this study is to identify the factors that influenced the number of tourist arrival in Pahang that leads towards focusing on the certain aspects that will play a role in order to boost the economic condition. This kind of study also will be helpful to know the performance of tourism industry in this state. The main objective of this research is to identify the level of foreigner satisfaction towards Tourism Malaysia Pahang’s services, to identify the mean for each independent variable, to rank the independent variables that contribute to foreigner satisfaction towards Tourism Malaysia Pahang’s services, and the last objective of this study is to identify the recommendation to increase the foreigner satisfaction at Tourism Malaysia Pahang parking space. This research is conducted by using non-probability sampling technique which is Exploratory and Descriptive Research. The populations in this study were the foreigners that come to Tourism Malaysia Pahang to ask and get some information about Pahang. In this study, researcher was decided to use Convenience Sampling which is a Non-Probability Sampling Technique that attempts to obtain a sample of convenient elements. 30 foreigners were selected to be the respondents by distributing each of them a questionnaire to answer. The conclusions of the research were from the outcome from the data analysis and findings, some of the recommendations are suggested for the benefit of future research.